Integrasi Nilai Islam Dalam Kurikulum Senior Secondary di Australian Islamic College - Muhammad Arifin Aprillianto; Imam Islamuddin (Journal of Islamic Education Studies, 2026)
This study aims to analyze the forms and strategies of integrating Islamic values into the Senior Secondary curriculum at the Australian Islamic College (AIC). Using a descriptive qualitative approach with document analysis methods, the research draws on two primary sources: the official AIC website and the 2023 Senior Handbook. The findings indicate that AIC implements an integrative and contextual Islamic education model in which Islamic values are internalized into all aspects of the curriculum and learning processes. Faith-based pedagogy serves as the foundation of instruction, while religious activities, character programs, and the school environment function as instruments for developing students' spirituality. AIC successfully combines the Australian national education system with the principles of tawhid, adab, and Islamic ethics without losing academic relevance. This model demonstrates that Islamic education can operate effectively within secular and multicultural contexts. The study contributes to the development of integrative Islamic education models and offers insights for Islamic educational institutions in Indonesia in designing curricula that balance academic competence and spiritual character formation.